Anticancer Activity of Combination of Benalu Belimbing (Macrosolen cochinensis) Extract and Sabrang Onion (Eleutherine palmifolia (L) Merr) on Cervical Cancer Hela Cell Line - Roihatul Mutiah; Anik Listiyana; Arief Suryadinata (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Benalu belimbing (Macrosolen cochinensis) and onion sabrang / onion dayak (Eleutherine palmifolia (L) Merr.) is a traditional medicinal plant that has been used by the community as a cancer drug from generation to generation. This study aims to prove scientifically about the anticancer potential from combination of both plants. Anticancer potential of the plant has been proven by testing the extract both in single form and in combination with Hela cells. While to know the selectivity of the extract to HeLa cell then extract is tested on normal cell Vero cell line. Furthermore, a combination test of both extracts was done using variation dose under IC50. The method used to determine anticancer activity was the MTT method. The results obtained in this study showed that ethanolic extract onion sabrang selectively able to inhibit the growth of cervical cancer cells HeLa on IC50: 40.36 μg / ml with 4.06 for the SI (selectivity index) value. While ethanolic extract of benalu belimbing bselectively can inhibit the growth of cervical cancer cells HeLa on IC50: 217.72 μg / ml with 5.77 for the SI (selectivity Index) value. The combination test of sabrang onion extract and extract of benalu belimbing showed that the combination was highly synergistic in combination dose of EBS 22.62 μg / ml and EBB 23.3 ug / ml with combination index 0.15. Whereas the combination doses having synergistic effects on combination doses 23.3 μg / ml for EBB and 11.31 μg / ml for EBS; 23.3 μg / ml EBB and 16.96 μg / ml EBS with a consecutive combination index; 0.51 and 0.64. From these results it can be concluded that the onion sabrang extract has anticancer effect on HeLa cells and selectively killing HeLa cells because the value of selectivity index is greater than 3. The result of the combination test of both extracts shows that the combination dose having strong synergistic effect, so that combination can be recommended for further research.